An Investigation of Utilization and Acceptance of LMS among Students of Teacher Education at AIOU Islamabad during COVID-19 Pandemic - Dr. Muhammad Aslam; Muhammad Sarwar; Muhammad Kamran (Journal of Peace, Development and Communication, 2022)
Learning Management Systems (LMS) is emerging internet technology that facilitating the instructions in blended, distance and face to face learning. The primary purpose of this paper was to explore the contribution of ease to use and usefulness of LMS in enhancing attitude towards use of LMS in teacher education at Allama Iqbal Open University (AIOU) Islamabad. The present study was a quantitative research and cross sectional survey design was used. The data were collected using adapted questionnaire of Trayek and Hassan (2013), which covered three variables ease of use, usefulness and attitude toward use of LMS. The respondents of this study were 310 Bachelor of Education (BEd) students of AIOU Islamabad and cluster random sampling technique was used for sampling. The data was collected through online Google survey form. Finally, the data was analyzed using SPSS and different statistics techniques were applied to meet the study objectives. The results indicated that perceived usefulness and ease of use of LMS had positive and significant contribution in nurturing attitude toward use of LMS among students of teacher education at AIOU Islamabad. Further, it was recommended that the management of AIOU Islamabad enhance the purposefulness, effectiveness and easy usability of LMS among students of teacher education.